Answer:
![a_n=a_{n-1}(\frac{1}{3})\\a_1=27](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%28%5Cfrac%7B1%7D%7B3%7D%29%5C%5Ca_1%3D27)
Step-by-step explanation:
A recursive formula is a formula in which each term is based on the previous term.
In a geometric sequence, each term is found by multiplying the previous term by a constant.
To get from 27 to 9, then from 9 to 3, etc., we would multiply by 1/3. This makes the common ratio 1/3.
The recursive formula for a geometric sequence is
, where
represents the general term,
, represents the previous term, and r represents the common ratio.
Plugging in our values, we have
![a_n=a_{n-1}(r)](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%28r%29)
We also have to indicate what the first term, a₁, is. In this sequence, it is 21. This gives us
![a_n=a_{n-1}(\frac{1}{3})\\a_1=27](https://tex.z-dn.net/?f=a_n%3Da_%7Bn-1%7D%28%5Cfrac%7B1%7D%7B3%7D%29%5C%5Ca_1%3D27)